2016
DOI: 10.1371/journal.pone.0147972
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use and Storage Patterns by Patients after Hospital Discharge following Surgery

Abstract: IntroductionOpioid-based analgesic therapy represents a cornerstone of pain management after surgery. The recent rise in opioid sales and opioid overdoses suggests it is important to maximize the safety of opioid prescribing after surgery. Given that patients may live with other family members in the home, safe storage and appropriate disposal of excess opioids after hospital discharge are necessary to prevent unintended secondary exposures. Identifying characteristics of patients who are likely to be prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
275
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(300 citation statements)
references
References 22 publications
7
275
2
4
Order By: Relevance
“…Bates et al, surveyed adult patients who underwent surgery in a urology practice and showed that only 58.0% of the prescribed pain medication was used and 67.0% of participants had excess medication [5] . In a cohort study by Bartels and colleagues, 53.0% of participants reported taking fewer than five opioid tablets following a cesarean delivery and 45.0% reported the same following thoracic surgery [9]. Based on these studies and our own findings, surgeons in a variety of specialties appear to be overprescribing opioid analgesia, leading to an excess of medication in the home.…”
Section: Discussionmentioning
confidence: 69%
“…Bates et al, surveyed adult patients who underwent surgery in a urology practice and showed that only 58.0% of the prescribed pain medication was used and 67.0% of participants had excess medication [5] . In a cohort study by Bartels and colleagues, 53.0% of participants reported taking fewer than five opioid tablets following a cesarean delivery and 45.0% reported the same following thoracic surgery [9]. Based on these studies and our own findings, surgeons in a variety of specialties appear to be overprescribing opioid analgesia, leading to an excess of medication in the home.…”
Section: Discussionmentioning
confidence: 69%
“…1015 Among the prospective studies considered for this review, we identified duplicate reports for one study 15, 16 and excluded three others 1719 because of an inability to distinguish surgical from non-surgical reports of unused opioid medications.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study examined patients’ concern about addiction, with 8% of thoracic surgery patients avoiding opioids for this reason. 10 …”
Section: Resultsmentioning
confidence: 99%
“…37 A study including thoracic and gynecologic surgery patients showed that 83 percent had leftover opioid medication and 71 to 73 percent stored the leftovers unsafely. 38 This unsafe handling of opioids is not unique to surgical patients—a large proportion of oncology patients 39 and those receiving opioids in the emergency room 40 did not dispose of or store their medications properly. Because most people with prescription opioid use disorder get them from friends and family, it is reasonable to conclude that our postoperative analgesia prescription practices are making a significant contribution to the supply of illicit opioids.…”
Section: Opioid Risk and Surgerymentioning
confidence: 99%